DETERMINATION OF SOME ENVIRONMENTAL FACTORS RELATED TO SEX RATIO OF BROWN SWISS CALVES - I. Yilmaz; E. Eyduran; A. Kaygisiz (Journal of Animal and Plant Sciences, 2010)
The aim of this study is to determine the environmental factors related to sex of calves born from Brown-Swiss cattle reared at Malya (M) and Konuklar (K) State Farms in Türkiye. A total of 7055 calves (1861 calves for K and 5194 calves for M state farms) were used as animal material. Unlike previous studies, a new ratio called “Relative Female Ratio (RFR)” (the superiority of female to male calves) was firstly suggested in this study for dairy cattle. The data on sex of all these calves, calving year, season, and parity of their dams were recorded. By using G statistic, an alternative of Pearson Chi-Square statistic, (which test an association between two categorical variables), calving year-sex, calving season-sex, parity-sex and sire-sex associations were examined for these two state farms. The proportions of male and female calves born in K and M state farms were 50.05:49.95 and 52.47:47.53, respectively. RFR values for K and M state farms were 0.998 (942 female calves/944 male calves) and 0.906 (2474 female calves/2731 male calves).When all the calves were taken into consideration, no significant association between state and sex was found.  In K state farm, when probabilities of G statistic were examined, calving year-sex, calving season-sex, parity-sex, and sire-sex associations were non-significant. In M state farm, according to probabilities of G statistic, only calving year-sex association was found to be important (P<0.05), but calving season-sex, parity-sex and sire-sex associations were non-significant. As a result, it is hoped that results obtained from the current study will be beneficial for later scientific studies to be conducted on Secondary Sex Ratio (SSR) and RFR in the future.
Keywords: Secondary sex ratio; dairy cattle; Relative Female Ratio (RFR)